PEMETAAN SEBARAN MINERAL HEMATIT (Fe2O3) PADA ENDAPAN BAUKSIT DI KECAMATAN SANDAI, KALIMANTAN BARAT - Putra, Yoga Abdul Malik; Muhardi; Perdana, Radhitya (Jurnal Teknologi Mineral dan Batubara, 2024)
Hematite (Fe2O3) is one of the minerals in bauxite deposits with a content of 20-45%. Estimation of hematite (Fe2O3) distribution over a large area with limited sample availability can be conducted using the interpolation method. This study aims to map and estimate the distribution of hematite (Fe2O3), ore thickness, and overburden thickness at Bukit Zahra, Sandai District, Ketapang Regency, West Kalimantan Province. The interpolation method in this study uses the inverse distance weighted (IDW) method, while the power test uses the calculation of the smallest root mean squared error (RMSE). The estimation results show the highest hematite (Fe2O3) content in the bauxite deposit of 20-25% is located at an elevation of 22-62 m, while the lowest hematite (Fe2O3) content of 0-6% is located at an elevation of 22-30 m. The mapping results show a maximum ore thickness of 7-9 m at an elevation of 46-62 m, while the minimum ore thickness of 0-1 m is at an elevation of 22-54 m. The maximum thickness of overburden is 6-8 m at an elevation of 38-46 m, while the minimum thickness of overburden is 0-1 m at an elevation of 22-62 m. The mapping results also show that the distribution of hematite (Fe2O3), ore, and overburden in the research site is on a gentle to steep slope.